A Comment on the Recent Circular Letter from the Congregation for Divine Worship and the Discipline of the Sacraments concerning dispensation from priestly obligations and of diacons from the impediment of orders - Read, Gordon F. (Canon Law Society newsletter, 1997)
Kommentar zum Rundbrief der Kleruskongregation zu Fragen der Laisierung und der Wiederheirat ständiger Diakone